An internal water-based nanosilicate self-healing anti-cracking densifier for cement-based materials and a preparation method thereof

CN117720298BActive Publication Date: 2026-10-09SUZHOU GUARDEX NEW MATERIAL TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311692101.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-11
Publication Date
2026-10-09
Estimated Expiration
2043-12-11

AI Technical Summary

Technical Problem

[0003]为了解决内掺水型密实剂兼顾抗裂和自愈合的问题,本申请提供一种用于水泥基材料的内掺水性纳米硅酸盐自愈合抗裂密实剂及其制备方法

Benefits of technology

1、本申请的密实剂高性能防水、逆向成长,反向渗透,迎背双防水;具有自愈合功能;本品为水剂,可直接添加在混凝土中,施工方便,计量准确,搅拌均匀,不额外增加搅拌时间,不需要做找平和防水保护层,省时省工;无机材料不老化,效果稳定,能够抗硫酸盐侵蚀,抗氯离子渗透,与混凝土结构体同寿命;提高混凝土防水抗渗性能,满足《地下工程防水技术规范》所规定的各种防水设防等级防水混凝土的防水抗渗要求,更适于要求抗渗等级高的防水工程,具有防水同步性,抗压、抗折强度好,耐酸碱盐,耐腐蚀;产品绿色环保,以水为分散体,无毒、无味、无污染,可用于饮水工程;对大体积混凝土,早期水化热最大峰值的时间得到了极大的推迟,极大的降低了水化热的温度应力,有效避免和减少混凝土的温度裂缝。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004599514920000101
    Figure BDA0004599514920000101
  • Figure BDA0004599514920000111
    Figure BDA0004599514920000111
Patent Text Reader

Abstract

The application relates to an internal-mixing water-based nanosilicate self-healing anti-cracking densifying agent for cement-based materials and a preparation method thereof. The internal-mixing water-based nanosilicate self-healing anti-cracking densifying agent comprises the following raw materials in parts by weight: sodium silicate 14-16 parts, potassium silicate 10-13 parts, an expansion component 5.54-6.55 parts, a hydration reaction inhibitor 5.5-7 parts, a hydration reaction promoter 0.02-0.06 parts, a hydration heat inhibitor 0.13-0.20 parts, an air entraining agent 0.06-0.09 parts and deionized water 57-65 parts. The internal-mixing water-based nanosilicate self-healing anti-cracking densifying agent has the functions of anti-cracking and self-healing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to a concrete densifying material, and more specifically, to an internally hydrated nano-silicate self-healing crack-resistant densifying agent for cement-based materials and its preparation method. Background Technology

[0002] Commercially available inorganic water-based penetrating crystalline materials are primarily composed of nano-silicates and possess self-healing properties. However, they can only be applied externally, and their penetration depth into concrete is generally only a few millimeters, resulting in limited protective effects compared to internally adsorbed self-healing products. Currently, most internally adsorbed self-healing products on the market are powdered cement-based penetrating crystalline waterproofing agents. Therefore, their use in mixing plants generates dust pollution, which is not environmentally friendly. Furthermore, powdered products are difficult to disperse evenly when mixed with concrete. These cement-based penetrating crystalline waterproofing agents only possess crack self-healing capabilities and do not have crack-resistant properties. Meanwhile, most liquid waterproofing agents on the market are crack-resistant agents conforming to the JC474-2008 standard and do not possess crack self-healing capabilities. Therefore, in summary, providing an internally adsorbed water-based nano-silicate self-healing crack-resistant densifying agent for cement-based materials has significant social and economic benefits. It can effectively reduce cracks in the early stages and self-heal when cracks appear later. Furthermore, the product itself is an inorganic liquid, environmentally friendly, easy to apply and mix, disperses evenly, is highly efficient, and has the same lifespan as the structure. Summary of the Invention

[0003] To address the issue of combining crack resistance and self-healing in water-infused densifiers, this application provides a water-infused nano-silicate self-healing crack-resistant densifier for cement-based materials and its preparation method.

[0004] In a first aspect, this application provides an internally incorporated water-based nano-silicate self-healing crack-resistant densifier for cement-based materials, comprising the following components in parts by weight: 14-16 parts sodium silicate, 10-13 parts potassium silicate, 5.54-6.55 parts expansion component, 5.5-7 parts hydration reaction inhibitor, 0.02-0.06 parts hydration reaction promoter, 0.13-0.20 parts hydration heat inhibitor, 0.06-0.09 parts air-entraining agent, and 57-65 parts deionized water.

[0005] By adopting the above-mentioned scheme, the hydration reaction inhibitor suppresses the reaction between silicates and calcium ions during concrete mixing; the hydration reaction accelerator promotes the reaction between calcium ions and silicate ions when cracks appear in the later stage of concrete; the hydration heat inhibitor reduces cracks caused by excessive temperature during cement hydration; the air-entraining agent improves the uniformity of cement, thereby further improving the strength and impermeability of cement; the reaction between sodium silicate, potassium silicate, and calcium hydroxide formed during cement hydration promotes the hydration of unhydrated cement particles, generating calcium silicate crystals and gels that block pores, effectively preventing water molecule penetration, thereby improving the impermeability of concrete, achieving the effect of self-healing cracks, and also improving the strength of concrete. All components are soluble in water, and the resulting compactor is high-performance waterproof, environmentally friendly, and has stable effects, with both crack resistance and self-healing functions.

[0006] In one specific implementation, the expanding component comprises 3.5-4 parts aluminum sulfate, 2-2.5 parts ferric sulfate, and 0.04-0.05 parts liquid magnesium oxide.

[0007] Aluminum sulfate, ferric sulfate, and liquid magnesium oxide are expanding components. When cement paste hydrates, they form microcrystals and expand, filling cracks caused by cement shrinkage. They can effectively fill early cracks in concrete and prolong the waterproofing effect. By limiting the mass to a certain proportion, the self-healing effect on crack filling is good. When used together with sodium silicate and potassium silicate, early crack filling and full healing of later cracks are achieved, thus realizing long-term impermeability of cement-based materials.

[0008] In one specific feasible implementation, the hydration reaction inhibitor comprises 3-4 parts sodium gluconate and 2.5-3 parts sucrose.

[0009] By adopting the above-mentioned approach, sodium gluconate and sucrose, being highly polar, adsorb onto the surface of cement. They can also react with metal ions in cement to form colloids, creating multi-layered molecular films that hinder the hydration reaction. Furthermore, they inhibit the solubility of gypsum in cement, further suppressing the hydration reaction of silicate and calcium ions during concrete mixing.

[0010] In one specific feasible implementation, the hydration reaction promoter includes 0.01-0.03 parts of boric acid and 0.01-0.03 parts of citric acid.

[0011] In one specific implementation, the hydration reaction promoter is boric acid and citric acid, and the mass ratio of boric acid to citric acid is (1-3):1.

[0012] The hydration reaction accelerator is a weak acid. When the compactor is prepared, the corresponding salt is generated. After the hydration reaction, it dissolves in the formed concrete. When cracks appear in the concrete later and water seeps in, it will dissolve in the water. Because it is a weak acid salt, it will undergo a hydrolysis reaction, which will generate the corresponding acid to promote the reaction of unreacted calcium ions in the cracks, thereby improving the self-healing effect.

[0013] Preferably, a mixture of boric acid and citric acid in a mass ratio of (1-3):1 is more effective as a hydration reaction promoter. Boric acid and citric acid have similar acid strengths, resulting in consistent hydrolysis of their respective weak acid salts. Adding boric acid and citric acid in this ratio ensures that the initial inhibition of the hydration reaction is not affected, and the reaction of calcium ions is promoted during the self-healing process, thus accelerating healing. The applicant's experiments have demonstrated that a 3:1 mass ratio of boric acid and citric acid yields the best results. This is likely because the acidity is optimal at this ratio, ensuring no impact on the inhibition of the hydration reaction in the early stages and maximizing the promoting effect in the later stages.

[0014] In one specific feasible implementation, the heat of hydration inhibitor comprises 0.1-0.15 parts sodium tripolyphosphate and 0.03-0.05 parts ethylenediaminetetraacetic acid.

[0015] In one specific feasible implementation, the hydration heat inhibitor is sodium tripolyphosphate and EDTA, and the mass ratio of sodium tripolyphosphate to EDTA is (2-5):1.

[0016] Ethylenediaminetetraacetic acid (EDTA) contains a large number of hydroxyl groups, which allows it to easily penetrate into the interior of cement. It forms complexes with calcium ions, delaying the formation of cement-based aggregates and reducing the rate of hydration reaction. This prevents excessive heat generated during hydration from causing the cement to shrink and crack due to temperature changes. Sodium tripolyphosphate has good fluidity, which can improve the dispersibility of cement. Better dispersion of silicates in cement allows for uniform hydration reaction, preventing cracks caused by uneven temperature. It also improves the workability of cement. More importantly, sodium tripolyphosphate chelates with metal ions in cement to form chelates, blocking calcium ions and further delaying the formation of cement-based aggregates, reducing the rate of hydration reaction, and mitigating heat generation.

[0017] Preferably, the hydration heat inhibitors are sodium tripolyphosphate and EDTA, and the mass ratio of sodium tripolyphosphate to ethylenediaminetetraacetic acid is (2-5):1. Sodium tripolyphosphate and EDTA complement each other based on their different complexation rates and stability. Besides dispersing sodium silicate and potassium silicate to make the hydration reaction more uniform, they not only reduce the rate of the hydration reaction and slow down heat generation, but also act as a seepage preventer and fill gaps.

[0018] In one specific feasible embodiment, the air-entraining agent comprises 0.05-0.07 parts of sodium dodecylbenzenesulfonate and 0.01-0.02 parts of sodium α-olefin sulfonate.

[0019] In one specific feasible embodiment, the air-entraining agent is sodium dodecylbenzenesulfonate and sodium α-alkenylsulfonate, and the mass ratio of sodium dodecylbenzenesulfonate to sodium α-alkenylsulfonate is (2.5-7):1.

[0020] Sodium dodecylbenzenesulfonate and sodium α-alkenylsulfonate (AOS) possess excellent surface activity, capable of generating abundant microfoams. They regulate the pore structure of cementitious materials, reduce capillary action, prevent water penetration, and improve the impermeability of cement. They can also alleviate internal stress in cement, improve its fluidity and plasticity, thereby reducing cracking and shrinkage, and exhibit high air entrainment efficiency. Sodium dodecylbenzenesulfonate has high foam strength and can improve cement dispersibility by influencing electrostatic attraction. AOS has a lower critical micelle concentration, allowing for the addition of smaller amounts to produce foam. Furthermore, the bubbles produced by both are relatively uniform in size, further enhancing the strength and impermeability of the cement.

[0021] Preferably, sodium dodecylbenzenesulfonate and sodium α-alkenylsulfonate are used in a mixture at a mass ratio of (2.5-7):1. This component ratio ensures that the resulting cement exhibits micro-foaming over a longer period, has a good pore structure, requires less dodecyl air-entraining agent, and exhibits strong impermeability.

[0022] Secondly, this application provides a method for preparing an internally incorporated water-based nano-silicate self-healing crack-resistant densifier for cement-based materials, comprising the following steps: S1: Add swelling component, hydration reaction inhibitor, hydration reaction promoter, hydration heat inhibitor, and air-entraining agent to deionized water, and stir to obtain a mixture; S2: Add sodium silicate and potassium silicate to the mixture obtained in S1, stir evenly, and obtain a densifying agent.

[0023] By adopting the above technical solution, the preparation method is simple. It only requires simple stirring according to the mass ratio to make the solid and liquid mix evenly to form a stable and homogeneous solution. This reduces production costs and simplifies the production process. The resulting densifier has stable performance and good application effect.

[0024] The densifier dissolves quickly, volatilizes minimally, does not deteriorate, and does not cause side reactions.

[0025] In summary, this application has the following beneficial effects: 1. The densifying agent of this application provides high-performance waterproofing, reverse growth, reverse penetration, and double waterproofing (both front and back); it has self-healing function; this product is a water-based agent that can be directly added to concrete, making construction convenient, accurate in measurement, and uniform in mixing without adding extra mixing time, eliminating the need for leveling and waterproof protective layers, saving time and labor; the inorganic material does not age, has stable effects, resists sulfate erosion and chloride ion penetration, and has the same lifespan as the concrete structure; it improves the waterproof and seepage-resistant performance of concrete, meeting the waterproof and seepage-resistant requirements of various waterproofing design levels of waterproof concrete as specified in the "Technical Specification for Waterproofing of Underground Engineering," and is more suitable for waterproofing projects requiring high seepage resistance. It has simultaneous waterproofing, good compressive and flexural strength, and is resistant to acids, alkalis, salts, and corrosion; the product is green and environmentally friendly, using water as a dispersion, non-toxic, odorless, and pollution-free, and can be used in drinking water projects; for large-volume concrete, the time of the maximum peak of early hydration heat is greatly delayed, significantly reducing the temperature stress of hydration heat and effectively avoiding and reducing temperature cracks in concrete.

[0026] 2. By specifying the exact composition of the expansion component, hydration reaction inhibitor, hydration reaction promoter, hydration heat inhibitor, and air-entraining agent, this application prepares a densifying agent that further enhances its anti-permeability and self-healing effects. Detailed Implementation

[0027] Unless otherwise specified, the experimental reagents used in the preparation examples, embodiments, and comparative examples are all from commercially available brands or obtained through conventional preparation processes. Example

[0028] Example 1 S1: Add 0.10g sodium tripolyphosphate, 0.03g EDTA, 3.5g aluminum sulfate, 2.0g ferric sulfate, 0.04g liquid magnesium oxide, 3.5g sodium gluconate, 2.7g sucrose, 0.02g boric acid, 0.02g citric acid, 0.06g sodium dodecylbenzenesulfonate, and 0.015g AOS to 60g of deionized water. Stir continuously during the addition process until all components are completely dissolved. The stirring temperature is 25℃ to obtain a mixed solution. S2: Add 16g of sodium silicate and 10g of potassium silicate to the mixture obtained in S1, stir evenly, and obtain a self-healing crack-resistant densifying agent.

[0029] Example 2 S1: Add 0.10g sodium tripolyphosphate, 0.03g EDTA, 3.5g aluminum sulfate, 2.0g ferric sulfate, 0.04g liquid magnesium oxide, 3.5g sodium gluconate, 2.7g sucrose, 0.02g boric acid, 0.02g citric acid, 0.06g sodium dodecylbenzenesulfonate, and 0.015g AOS to 60g of deionized water. Stir continuously during the addition process until all components are completely dissolved. The stirring temperature is 25℃ to obtain a mixed solution. S2: Add 14g of sodium silicate and 13g of potassium silicate to the mixture obtained in S1, stir evenly, and obtain a self-healing crack-resistant densifying agent.

[0030] Example 3 S1: Add 0.10g sodium tripolyphosphate, 0.03g EDTA, 4.0g aluminum sulfate, 2.0g ferric sulfate, 0.04g liquid magnesium oxide, 3.5g sodium gluconate, 2.7g sucrose, 0.02g boric acid, 0.02g citric acid, 0.06g sodium dodecylbenzenesulfonate, and 0.015g AOS to 60g of deionized water. Stir continuously during the addition process until all components are completely dissolved. The stirring temperature is 25℃ to obtain a mixed solution. S2: Add 14g of sodium silicate and 10g of potassium silicate to the mixture obtained in S1, stir evenly, and obtain a self-healing crack-resistant densifying agent.

[0031] Example 4 S1: Add 0.10g sodium tripolyphosphate, 0.03g EDTA, 3.5g aluminum sulfate, 2.5g ferric sulfate, 0.04g liquid magnesium oxide, 3.5g sodium gluconate, 2.7g sucrose, 0.02g boric acid, 0.02g citric acid, 0.06g sodium dodecylbenzenesulfonate, and 0.015g AOS to 60g of deionized water. Stir continuously during the addition process until all components are completely dissolved. The stirring temperature is 25℃ to obtain a mixed solution. S2: Add 14g of sodium silicate and 10g of potassium silicate to the mixture obtained in S1, stir evenly, and obtain a self-healing crack-resistant densifying agent.

[0032] Example 5 S1: Add 0.10g sodium tripolyphosphate, 0.03g EDTA, 3.5g aluminum sulfate, 2.0g ferric sulfate, 0.05g liquid magnesium oxide, 3.5g sodium gluconate, 2.7g sucrose, 0.02g boric acid, 0.02g citric acid, 0.06g sodium dodecylbenzenesulfonate, and 0.015g AOS to 60g of deionized water. Stir continuously during the addition process until all components are completely dissolved. The stirring temperature is 25℃ to obtain a mixed solution. S2: Add 14g of sodium silicate and 10g of potassium silicate to the mixture obtained in S1, stir evenly, and obtain a self-healing crack-resistant densifying agent.

[0033] Example 6 S1: Add 0.10g sodium tripolyphosphate, 0.03g EDTA, 3.5g aluminum sulfate, 2.0g ferric sulfate, 0.04g liquid magnesium oxide, 6.2g potassium dihydrogen phosphate, 0.02g boric acid, 0.02g citric acid, 0.06g sodium dodecylbenzenesulfonate, and 0.015g AOS to 60g of deionized water. Stir continuously during the addition process until all components are completely dissolved. The stirring temperature is 25℃ to obtain a mixed solution. S2: Add 16g of sodium silicate and 10g of potassium silicate to the mixture obtained in S1, stir evenly, and obtain a self-healing crack-resistant densifying agent.

[0034] Example 7 S1: Add 0.10g sodium tripolyphosphate, 0.03g EDTA, 3.5g aluminum sulfate, 2.0g ferric sulfate, 0.04g liquid magnesium oxide, 3.5g sodium gluconate, 2.7g sucrose, 0.04g diethanolamine monoisopropanolamine, 0.06g sodium dodecylbenzenesulfonate, and 0.015g AOS to 60g of deionized water. Stir continuously during the addition process until all components are completely dissolved. The stirring temperature is 25℃ to obtain a mixture. S2: Add 16g of sodium silicate and 10g of potassium silicate to the mixture obtained in S1, stir evenly, and obtain a self-healing crack-resistant densifying agent.

[0035] Example 8 S1: Add 0.13g sodium monofluorophosphate, 3.5g aluminum sulfate, 2.0g ferric sulfate, 0.04g liquid magnesium oxide, 3.5g sodium gluconate, 2.7g sucrose, 0.02g boric acid, 0.02g citric acid, 0.06g sodium dodecylbenzenesulfonate, and 0.015g AOS to 60g of deionized water. Stir continuously during the addition process until all components are completely dissolved. The stirring temperature is 25℃ to obtain a mixed solution. S2: Add 16g of sodium silicate and 10g of potassium silicate to the mixture obtained in S1, stir evenly, and obtain a self-healing crack-resistant densifying agent.

[0036] Example 9 S1: Add 0.13g sodium tripolyphosphate, 3.5g aluminum sulfate, 2.0g ferric sulfate, 0.04g liquid magnesium oxide, 3.5g sodium gluconate, 2.7g sucrose, 0.02g boric acid, 0.02g citric acid, 0.06g sodium dodecylbenzenesulfonate, and 0.015g AOS to 60g of deionized water. Stir continuously during the addition process until all components are completely dissolved. The stirring temperature is 25℃ to obtain a mixed solution. S2: Add 16g of sodium silicate and 10g of potassium silicate to the mixture obtained in S1, stir evenly, and obtain a self-healing crack-resistant densifying agent.

[0037] Example 10 S1: Add 0.13g EDTA, 3.5g aluminum sulfate, 2.0g ferric sulfate, 0.04g liquid magnesium oxide, 3.5g sodium gluconate, 2.7g sucrose, 0.02g boric acid, 0.02g citric acid, 0.06g sodium dodecylbenzenesulfonate, and 0.015g AOS to 60g of deionized water. Stir continuously during the addition process until all components are completely dissolved. The stirring temperature is 25℃ to obtain a mixed solution. S2: Add 16g of sodium silicate and 10g of potassium silicate to the mixture obtained in S1, stir evenly, and obtain a self-healing crack-resistant densifying agent.

[0038] Example 11 S1: Add 0.085g sodium tripolyphosphate, 0.045g EDTA, 3.5g aluminum sulfate, 2.0g ferric sulfate, 0.04g liquid magnesium oxide, 3.5g sodium gluconate, 2.7g sucrose, 0.02g boric acid, 0.02g citric acid, 0.06g sodium dodecylbenzenesulfonate, and 0.015g AOS to 60g of deionized water. Stir continuously during the addition process until all components are completely dissolved. The stirring temperature is 25℃ to obtain a mixed solution. S2: Add 16g of sodium silicate and 10g of potassium silicate to the mixture obtained in S1, stir evenly, and obtain a self-healing crack-resistant densifying agent.

[0039] Example 12 S1: Add 0.10g sodium tripolyphosphate, 0.03g EDTA, 3.5g aluminum sulfate, 2.0g ferric sulfate, 0.04g liquid magnesium oxide, 3.5g sodium gluconate, 2.7g sucrose, 0.02g boric acid, 0.02g citric acid, and 0.075g aluminum chloride to 60g deionized water. Stir continuously during the addition process until all components are completely dissolved. The stirring temperature is 25℃ to obtain a mixed solution. S2: Add 16g of sodium silicate and 10g of potassium silicate to the mixture obtained in S1, stir evenly, and obtain a self-healing crack-resistant densifying agent.

[0040] Example 13 S1: Add 0.10g sodium tripolyphosphate, 0.03g EDTA, 3.5g aluminum sulfate, 2.0g ferric sulfate, 0.04g liquid magnesium oxide, 3.5g sodium gluconate, 2.7g sucrose, 0.02g boric acid, 0.02g citric acid, and 0.075g sodium dodecylbenzenesulfonate to 60g of deionized water. Stir continuously during the addition process until all components are completely dissolved. The stirring temperature is 25℃ to obtain a mixed solution. S2: Add 16g of sodium silicate and 10g of potassium silicate to the mixture obtained in S1, stir evenly, and obtain a self-healing crack-resistant densifying agent.

[0041] Example 14 S1: Add 0.10g sodium tripolyphosphate, 0.03g EDTA, 3.5g aluminum sulfate, 2.0g ferric sulfate, 0.04g liquid magnesium oxide, 3.5g sodium gluconate, 2.7g sucrose, 0.02g boric acid, 0.02g citric acid, and 0.075g AOS to 60g of deionized water. Stir continuously during the addition process until all components are completely dissolved. The stirring temperature is 25℃ to obtain a mixed solution. S2: Add 16g of sodium silicate and 10g of potassium silicate to the mixture obtained in S1, stir evenly, and obtain a self-healing crack-resistant densifying agent.

[0042] Example 15 S1: Add 0.10g sodium tripolyphosphate, 0.03g EDTA, 3.5g aluminum sulfate, 2.0g ferric sulfate, 0.04g liquid magnesium oxide, 3.5g sodium gluconate, 2.7g sucrose, 0.02g boric acid, 0.02g citric acid, 0.055g sodium dodecylbenzenesulfonate, and 0.020g AOS to 60g of deionized water. Stir continuously during the addition process until all components are completely dissolved. The stirring temperature is 25℃ to obtain a mixed solution. S2: Add 16g of sodium silicate and 10g of potassium silicate to the mixture obtained in S1, stir evenly, and obtain a self-healing crack-resistant densifying agent.

[0043] Example 16 S1: Add 0.10g sodium tripolyphosphate, 0.03g EDTA, 2.5g aluminum sulfate, 3.5g ferric sulfate, 0.04g liquid magnesium oxide, 3.5g sodium gluconate, 2.7g sucrose, 0.02g boric acid, 0.02g citric acid, 0.06g sodium dodecylbenzenesulfonate, and 0.015g AOS to 60g of deionized water. Stir continuously during the addition process until all components are completely dissolved. The stirring temperature is 25℃ to obtain a mixed solution. S2: Add 14g of sodium silicate and 10g of potassium silicate to the mixture obtained in S1, stir evenly, and obtain a self-healing crack-resistant densifying agent.

[0044] Example 17 S1: Add 0.10g sodium tripolyphosphate, 0.03g EDTA, 5g aluminum sulfate, 1.0g ferric sulfate, 0.04g liquid magnesium oxide, 3.5g sodium gluconate, 2.7g sucrose, 0.02g boric acid, 0.02g citric acid, 0.06g sodium dodecylbenzenesulfonate, and 0.015g AOS to 60g of deionized water. Stir continuously during the addition process until all components are completely dissolved. The stirring temperature is 25℃ to obtain a mixed solution. S2: Add 14g of sodium silicate and 10g of potassium silicate to the mixture obtained in S1, stir evenly, and obtain a self-healing crack-resistant densifying agent.

[0045] Example 18 S1: Add 0.10g sodium tripolyphosphate, 0.03g EDTA, 4.02g aluminum sulfate, 2.0g ferric sulfate, 0.02g liquid magnesium oxide, 3.5g sodium gluconate, 2.7g sucrose, 0.02g boric acid, 0.02g citric acid, 0.06g sodium dodecylbenzenesulfonate, and 0.015g AOS to 60g of deionized water. Stir continuously during the addition process until all components are completely dissolved. The stirring temperature is 25℃ to obtain a mixed solution. S2: Add 14g of sodium silicate and 10g of potassium silicate to the mixture obtained in S1, stir evenly, and obtain a self-healing crack-resistant densifying agent.

[0046] Example 19 S1: Add 0.10g sodium tripolyphosphate, 0.03g EDTA, 3.5g aluminum sulfate, 2.0g ferric sulfate, 0.04g liquid magnesium oxide, 3.5g sodium gluconate, 2.7g sucrose, 0.04g boric acid, 0.06g sodium dodecylbenzenesulfonate, and 0.015g AOS to 60g of deionized water. Stir continuously during the addition process until all components are completely dissolved. The stirring temperature is 25℃ to obtain a mixed solution. S2: Add 16g of sodium silicate and 10g of potassium silicate to the mixture obtained in S1, stir evenly, and obtain a self-healing crack-resistant densifying agent.

[0047] Example 20 S1: Add 0.10g sodium tripolyphosphate, 0.03g EDTA, 3.5g aluminum sulfate, 2.0g ferric sulfate, 0.04g liquid magnesium oxide, 3.5g sodium gluconate, 2.7g sucrose, 0.04g citric acid, 0.06g sodium dodecylbenzenesulfonate, and 0.015g AOS to 60g of deionized water. Stir continuously during the addition process until all components are completely dissolved. The stirring temperature is 25℃ to obtain a mixed solution. S2: Add 16g of sodium silicate and 10g of potassium silicate to the mixture obtained in S1, stir evenly, and obtain a self-healing crack-resistant densifying agent.

[0048] Example 21 S1: Add 0.10g sodium tripolyphosphate, 0.03g EDTA, 3.5g aluminum sulfate, 2.0g ferric sulfate, 0.04g liquid magnesium oxide, 3.5g sodium gluconate, 2.7g sucrose, 0.02g boric acid, 0.02g phosphoric acid, 0.06g sodium dodecylbenzenesulfonate, and 0.015g AOS to 60g of deionized water. Stir continuously during the addition process until all components are completely dissolved. The stirring temperature is 25℃ to obtain a mixed solution. S2: Add 16g of sodium silicate and 10g of potassium silicate to the mixture obtained in S1, stir evenly, and obtain a self-healing crack-resistant densifying agent.

[0049] Example 22 S1: Add 0.10g sodium tripolyphosphate, 0.03g EDTA, 3.5g aluminum sulfate, 2.0g ferric sulfate, 0.04g liquid magnesium oxide, 3.5g sodium gluconate, 2.7g sucrose, 0.02g boric acid, 0.02g acetic acid, 0.06g sodium dodecylbenzenesulfonate, and 0.015g AOS to 60g of deionized water. Stir continuously during the addition process until all components are completely dissolved. The stirring temperature is 25℃ to obtain a mixed solution. S2: Add 16g of sodium silicate and 10g of potassium silicate to the mixture obtained in S1, stir evenly, and obtain a self-healing crack-resistant densifying agent.

[0050] Example 23 S1: Add 0.10g sodium tripolyphosphate, 0.03g EDTA, 3.5g aluminum sulfate, 2.0g ferric sulfate, 0.04g liquid magnesium oxide, 3.5g sodium gluconate, 2.7g sucrose, 0.03g boric acid, 0.01g citric acid, 0.06g sodium dodecylbenzenesulfonate, and 0.015g AOS to 60g of deionized water. Stir continuously during the addition process until all components are completely dissolved. The stirring temperature is 25℃ to obtain a mixed solution. S2: Add 16g of sodium silicate and 10g of potassium silicate to the mixture obtained in S1, stir evenly, and obtain a self-healing crack-resistant densifying agent.

[0051] Example 24 S1: Add 0.10g sodium tripolyphosphate, 0.03g EDTA, 3.5g aluminum sulfate, 2.0g ferric sulfate, 0.04g liquid magnesium oxide, 3.5g sodium gluconate, 2.7g sucrose, 0.01g boric acid, 0.03g citric acid, 0.06g sodium dodecylbenzenesulfonate, and 0.015g AOS to 60g of deionized water. Stir continuously during the addition process until all components are completely dissolved. The stirring temperature is 25℃ to obtain a mixed solution. S2: Add 16g of sodium silicate and 10g of potassium silicate to the mixture obtained in S1, stir evenly, and obtain a self-healing crack-resistant densifying agent.

[0052] Comparative Example Comparative Example 1 S1: Add 0.10g sodium tripolyphosphate, 0.03g EDTA, 3.5g sodium gluconate, 2.7g sucrose, 0.02g boric acid, 0.02g citric acid, 0.06g sodium dodecylbenzenesulfonate, and 0.015g AOS to 60g deionized water. Stir continuously during the addition process until all components are completely dissolved. The stirring temperature is 25℃ to obtain a mixture. S2: Add 16g of sodium silicate and 15.54g of potassium silicate to the mixture obtained in S1, stir evenly, and obtain a self-healing crack-resistant densifying agent.

[0053] Comparative Example 2 S1: Add 0.10g sodium tripolyphosphate, 0.03g EDTA, 3.5g aluminum sulfate, 28g ferric sulfate, 0.04g liquid magnesium oxide, 3.5g sodium gluconate, 2.7g sucrose, 0.02g boric acid, 0.02g citric acid, 0.06g sodium dodecylbenzenesulfonate, and 0.015g AOS to 60g of deionized water. Stir continuously during the addition process until all components are completely dissolved. The stirring temperature is 25℃ to obtain a self-healing crack-resistant densifying agent.

[0054] Comparative Example 3 S1: Add 3.5g aluminum sulfate, 2.0g ferric sulfate, 0.04g liquid magnesium oxide, 3.5g sodium gluconate, 2.7g sucrose, 0.02g boric acid, 0.02g citric acid, 0.06g sodium dodecylbenzenesulfonate, and 0.015g AOS to 60.13g of deionized water. Stir continuously during the addition process until all components are completely dissolved. The stirring temperature is 25℃ to obtain a mixed solution. S2: Add 16g of sodium silicate and 10g of potassium silicate to the mixture obtained in S1, stir evenly, and obtain a self-healing crack-resistant densifying agent.

[0055] Comparative Example 4 S1: Add 0.10g sodium tripolyphosphate, 0.03g EDTA, 3.5g aluminum sulfate, 2.0g ferric sulfate, 0.04g liquid magnesium oxide, 0.02g boric acid, 0.02g citric acid, 0.06g sodium dodecylbenzenesulfonate, and 0.015g AOS to 66.2g of deionized water. Stir continuously during the addition process until all components are completely dissolved. The stirring temperature is 25℃ to obtain a mixed solution. S2: Add 16g of sodium silicate and 10g of potassium silicate to the mixture obtained in S1, stir evenly, and obtain a self-healing crack-resistant densifying agent.

[0056] Comparative Example 5 S1: Add 0.10g sodium tripolyphosphate, 0.03g EDTA, 3.5g aluminum sulfate, 2.0g ferric sulfate, 0.04g liquid magnesium oxide, 3.5g sodium gluconate, 2.7g sucrose, 0.06g sodium dodecylbenzenesulfonate, and 0.015g AOS to 60.04g deionized water. Stir continuously during the addition process until all components are completely dissolved. The stirring temperature is 25℃ to obtain a mixed solution. S2: Add 16g of sodium silicate and 10g of potassium silicate to the mixture obtained in S1, stir evenly, and obtain a self-healing crack-resistant densifying agent.

[0057] Performance testing was conducted by incorporating the self-healing crack-resistant densifiers prepared in Examples 1-24 and Comparative Examples 1-5 into the same cement-based concrete. Appropriate amounts of cement, crushed stone, sand, and densifier were weighed in a ratio of 0.5 kg: 0.8 kg: 0.8 kg: 0.01 kg. Compressive strength was tested according to standard GB / T-50081-2002 "Standard for Test Methods of Mechanical Properties of Ordinary Concrete". Macroscopic water permeability tests were performed on the concrete to test the impermeability of the corresponding concretes in Examples 1-24 and Comparative Examples 1-5. The test results are summarized in Table 1.

[0058] Table 1 In combination with Examples 1-24 and Comparative Examples 1-5, the densifier prepared in Examples 1-24 of this application exhibits high 28-day strength and good self-healing and impermeability performance in cement materials, making it more suitable for waterproofing projects requiring high impermeability levels.

[0059] As can be seen from Examples 1-24, the densifying agent of this application achieves a better seepage prevention effect by selecting appropriate types and ratios of expansion components, hydration heat inhibitors, hydration reaction inhibitors, and hydration reaction promoters. Boric acid and citric acid are selected as hydration reaction promoters, and a better seepage prevention effect is achieved when the mass ratio of boric acid to citric acid is 3:1.

[0060] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.

Claims

1. A water-admixed nano-silicate self-healing crack-resistant densifying agent for use in cement-based materials, characterized in that: The compacting agent comprises the following raw materials in parts by weight: 14-16 parts sodium silicate, 10-13 parts potassium silicate, 5.54-6.55 parts expansion component, 5.5-7 parts hydration reaction inhibitor, 0.02-0.06 parts hydration reaction promoter, 0.13-0.20 parts hydration heat inhibitor, 0.06-0.09 parts air-entraining agent, and 57-65 parts deionized water; The hydration reaction inhibitor is 3-4 parts sodium gluconate and 2.5-3 parts sucrose; The expansion component consists of 3.5-4 parts aluminum sulfate, 2-2.5 parts ferric sulfate, and 0.04-0.05 parts liquid magnesium oxide; The hydration reaction promoters are boric acid and citric acid, and the mass ratio of boric acid to citric acid is 3:

1. The hydration heat inhibitor is sodium tripolyphosphate and ethylenediaminetetraacetic acid, and the mass ratio of sodium tripolyphosphate to ethylenediaminetetraacetic acid is (2-5):

1.

2. The water-admixed nano-silicate self-healing crack-resistant densifier for cement-based materials according to claim 1, characterized in that: The air-entraining agent comprises 0.05-0.07 parts of sodium dodecylbenzenesulfonate and 0.01-0.02 parts of sodium α-olefin sulfonate.

3. The water-admixed nano-silicate self-healing crack-resistant densifier for cement-based materials according to claim 1, characterized in that: The air-entraining agent is sodium dodecylbenzenesulfonate and sodium α-alkenylsulfonate, and the mass ratio of sodium dodecylbenzenesulfonate to sodium α-alkenylsulfonate is (2.5-7):

1.

4. A method for preparing an internally incorporated water-based nano-silicate self-healing crack-resistant densifying agent for cement-based materials according to any one of claims 1-3, characterized in that: Preparation method Includes the following steps: S1: Add swelling component, hydration reaction inhibitor, hydration reaction promoter, hydration heat inhibitor, and air-entraining agent to deionized water, and stir to obtain a mixture; S2: Add sodium silicate and potassium silicate to the mixture obtained in S1, stir evenly, and obtain a densifying agent.

Citation Information

Patent Citations

  • Formula of concrete creak self-repair material and preparation technology

    CN101386508A

  • Anti-crack and anti-corrosion plasticizer composition and preparation method thereof

    CN102531458A

  • Self-healing inorganic nano anti-cracking permeability reducing agent and preparation method thereof

    CN116514451A